DdRAD Sequencing Sheds Light on Low Interspecific and High Intraspecific mtDNA Divergences in Two Groups of Caddisflies. Issue 5 (7th September 2021) - Salokannel, Juha; Lee, Kyung Min; Rinne, Aki; Mutanen, Marko
Abstract: Large-scale global efforts on DNA barcoding have repeatedly revealed unexpected patterns of variability in mtDNA, including deep intraspecific divergences and haplotype sharing between species. Understanding the evolutionary causes behind these patterns calls for insights from the nuclear genome. While building a near-complete DNA barcode library of Finnish caddisflies, a case of barcode-sharing and some cases of deep intraspecific divergences were observed. In this study, the Apatania zonella (Zetterstedt, 1840) group and three Limnephilus Leach, 1815 species were studied using double digest RAD sequencing (ddRAD-seq), morphology, and DNA barcoding. The results support the present species boundaries in the A. zonella group species. A morphologically distinct but mitogenetically nondistinct taxon related to parthenogenetic Apatania hispida (Forsslund, 1930) got only weak support for its validity as a distinct species. The morphology and genomic-scale data do not indicate cryptic diversity in any of the three Limnephilus species despite the observed deep intraspecific divergences in DNA barcodes. This demonstrates that polymorphism in mtDNA may not reflect cryptic diversity, but mitonuclear discordance due to other evolutionary causes.